Characterization of pain-related behaviors in a rat model of acute-to-chronic low back pain: single vs. multi-level disc injury - Barbe, Mary F.; Chen, Frank Liu; Loomis, Regina H.; Harris, Michele Y.; Kim, Brandon M.; Xie, Kevin; Hilliard, Brendan A.; McGonagle, Elizabeth R.; Bailey, Taylor D.; Gares, Ryan P.; Van Der Bas, Megan; Kalicharan, Betsy A.; et al. (Frontiers in Pain Research, 2024)
Low back pain is the most common type of chronic pain. We examined pain-related behaviors across 18 weeks in rats that received injury to one or two lumbar intervertebral discs (IVD) to determine if multi-level disc injuries enhance/prolong pain. Twenty-three Sprague-Dawley adult female rats were used: 8 received disc puncture (DP) of one lumbar IVD (L5/6, DP-1); 8 received DP of two lumbar IVDs (L4/5 & L5/6, DP-2); 8 underwent sham surgery. DP-2 rats showed local (low back) sensitivity to pressure at 6- and 12-weeks post-injury, and remote sensitivity to pressure (upper thighs) at 12- and 18-weeks and touch (hind paws) at 6, 12 and 18-weeks. DP-1 rats showed local and remote pressure sensitivity at 12-weeks only (and no tactile sensitivity), relative to Sham DP rats. Both DP groups showed reduced distance traveled during gait testing over multiple weeks, compared to pre-injury; only DP-2 rats showed reduced distance relative to Sham DP rats at 12-weeks. DP-2 rats displayed reduced positive interactions with a novel adult female rat at 3-weeks and hesitation and freezing during gait assays from 6-weeks onwards. At study end (18-weeks), radiological and histological analyses revealed reduced disc height and degeneration of punctured IVDs. Serum BDNF and TNFalpha levels were higher at 18-weeks in DP-2 rats, relative to Sham DP rats, increases that correlated positively with remote sensitivity in hind paws (tactile) and thighs (pressure). Thus, multi-level disc injuries resulted in earlier, prolonged and greater discomfort locally and remotely, than single-level disc injury. BDNF and TNFalpha may have contributing roles.